Health Risks of Food Additives (IntechOpen, 2024)
This Edited Volume Health Risks and Benefits of Food Additives - Recent Developments and Trends in Food Sector is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of Agricultural and Biological Sciences. The book comprises single chapters authored by various researchers and edited by an expert active in the Food Safety research area. All chapters are complete in themselves but united under a common research study topic. This publication aims to provide a thorough overview of the latest research effortsby international authors on Food Safety, and open new possible research paths for further novel developments.